The Effect Of Tangibles And Responsiveness On Customer Satisfaction At Pertamina Gas Stations In Padang City - Sri Yulia Putri; Ash Shadiq Egim (Yayasan Edukasi Cakrawala Nusantara, 2024)
This study aims to analyze the influence of tangible and responsiveness on customer satisfaction at Pertamina gas stations in Padang City. Customer satisfaction is a crucial factor in determining the success of service companies, particularly in building loyalty and improving service quality. This study employed a quantitative approach with a survey method, distributing questionnaires to 100 respondents, consumers of Pertamina gas stations in Padang City. Incidental sampling was used as the sampling technique. The results indicate that tangible and responsiveness partially influence customer satisfaction. Furthermore, both variables simultaneously have a significant influence on customer satisfaction. These findings indicate that the quality of physical facilities and employee responsiveness in providing fast and accurate service are important factors in increasing customer satisfaction